Extremely high anti‐Mullerian hormone levels detected during infertility workup revealing sex cord tumor with annular tubules and underlying Peutz–Jeghers syndrome: A case report. Issue 2 (27th November 2021) - Yucel Cicek, Ozge Senem; Gezer, Sener; Cakir, Ozgur; Hekimoglu Gurbuz, Rumeysa
Abstract: We report an infertile, but otherwise asymptomatic woman, whose extremely high anti‐Mullerian hormone (AMH) level detected during infertility investigation led to the diagnosis of sex cord tumor with annular tubules (SCTAT) which is a very rare sex cord‐stromal tumor (SCST) and eventually revealed a previously undiagnosed hereditary cancer syndrome, Peutz–Jeghers syndrome (PJS). A 33‐year‐old woman attended Kocaeli University ART Clinic for infertility evaluation. Her AMH level was 319.63 ng/ml. Detection of bilateral ovarian cysts required surgical evaluation. The histopathological examination of ovaries revealed SCTAT. The strong association of SCTAT with PJS raised the suspicion of this syndrome. Whole STK11 gene sequencing confirmed PJS diagnosis. AMH has become a widely used tool in the evaluation of infertile women. Clinicians dealing with infertility should be familiar with the utility of AMH measurement besides being a marker of ovarian reserve. Detection of high AMH concentrations should raise the suspicion of an SCST.